EFEKTIVITAS MEDIA BLACKBERRY MESSENGER SEBAGAI SALURAN PESAN DAKWAH LEMBAGA STUDI MAHASISWA ISLAM (LSMI) ALMADANI DI KALANGAN MAHASISWA FISIP UNIVERSITAS RIAU - Maya Sucitra Effendi; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research is to understand how Effectivenes of Blackberry Messenger Media as a channel Da’wah Message on institute study of Islamic Student (ALMADANI) among the Fisip Riau University student. With the present disclosure, the development of Da’wah should not be listening to lectures dealing directly with scholars, yet through the message through social media we can easily receive messages of Da’wah every time. One of these Da’wah messages from the media blackberry messenger sent by the Institute for the Study of Islamic Students ALMADANI student UR FISIP.This research metode has built with kuantitatif descriptive metode and the population is FISIP University of Riau students which related and contact with Almadani on blackberry messenger as a responden. Methods of data collection by field research (field research) by distributing a questionnaire, a questionnaire and a research library data.Researcher has formulated answered-hypothesis whic reveals the fact that the effectiveness of blackberry messenger media as a channel of LSMI AlMADANI Da’wah messages 4.11 the range of 3.4 - 4.2. The figure explains that the media used blackberry messenger ALMADANI effectively used as a means of Da’wah message channel among students FISIP UR.Keywords : Effectiveness, Blackberry Messenger, ALMADANI, FISIP Universitas Riau, Da’wah